Comparison of motivation factors in two wood processing companies - Faletar, Josip (Acta silvae et ligni, 2016)
This research analyzed the motivating and demotivating factors amongst employees in two wood processing companies. The research was conducted over the years 2014 and 2015 with a survey using a questionnaire containing six questions with available statements offered. The questions were closed-ended, and respondents used the four-level scale of importance for each statement. A total of 180 employees in each company were surveyed, and results were statistically processed by using the X2- test and cluster analysis. This study established that the motivation factors most important to employees between researched companies are significantly different. Employees were most concerned about social needs. Also, employees consider psychological circumstances of work to be very important. Employees' overall motivation can be linked to higher efficiency and higher quality production and business results, and such research should be conducted more often.
Keywords: lesna industrija; wood industry; personnel management; upravljanje kadrov; employees; motivacijski dejavniki; motivating factors; demotivacijski dejavniki; de-motivating factors